Stability of phenolic compounds, antioxidant activity and colour parameters of a coloured extract obtained from coloured-flesh potatoes. (January 2021) - Ercoli, Stefano; Cartes, Jennifer; Cornejo, Pablo; Tereucán, Gonzalo; Winterhalter, Peter; Contreras, Boris; Ruiz, Antonieta
Abstract: Potato ( Solanum tuberosum ) tubers stand out for their natural pigmentation granted by anthocyanins. There is currently little information about their stability in terms of concentration, antioxidant activity and colouration to certain storage factors; therefore, we aimed to analyse such variables during storage for four months under different pH and temperature conditions and in the presence or absence of light. In general, the most deleterious condition for maintaining total anthocyanins was under light at room temperature, which presented a decrease of 85%. In contrast, in liquid extracts the optimal storage conditions were 4 °C in the dark, with a loss of 4%. The antioxidant activity and colour analyses showed optimal stability in the liquid extracts. This would make it possible to deliver added value to purple fleshed potato extracts because they are a good source of natural antioxidant pigments with potential applications in the agri-food industry as an alternative to artificial dyes. Highlights: Flesh coloured potatoes have high concentration of total phenols. Anthocyanins in purple coloured potatoes are mainly petunidin derivatives. We analyzed the stability of a potato extract oriented to be used in food industry. Storage at light at room temperature strongly decreases the extract stability. Antioxidant activity and colour are most stable in liquid extracts.